The Influence of Trust in Government, Spiritual Intelligence and Social Norm on The Motivation to Pay Tax - Anugerah Suryani; Y. Yeselinda (Golden Ratio of Taxation Studies, 2021)
This research aims a). To find out the effect of trust in the government on the motivation to pay taxes at the North Makassar Tax Service Office; b). To find out the Effect of Spiritual Intelligence on the Motivation to Pay Taxes at the North Makassar Tax Service Office; c) To find out the effect of social norms on motivation to pay taxes at the North Makassar Tax Service Office; The analytical method used in this study is Multiple Linear Regression analysis. The sample in this study were 100 individual taxpayers at KPP Makassar Utara. The research results show that (1). Trust in the government has a positive and significant effect on motivation to pay taxes with a value of t count = 5,958 > t table = 1,660 with a significance level of 0.000. (2) Spiritual intelligence has a positive and significant effect on motivation to pay taxes at the North Makassar Tax Office with partial t count = 3,347 > t-table = 1,660 with a significance level of 0.001. (3). Social Norms have a positive and significant effect on the performance of employees of the Makassar State Wealth and Auction Service Office. the value of t count = 4,438 > t table = 1,660, with a significance level of 0.000, smaller than the level of α = 5%.